Geophysical Survey in Sub‐Saharan Africa: magnetic and Electromagnetic Investigation of the UNESCO World Heritage Site of Songo Mnara, Tanzania1. Issue 4 (1st May 2014) - Welham, K.; Fleisher, J.; Cheetham, P.; Manley, H.; Steele, C.; Wynne‐Jones, S.
ABSTRACT Magnetometry and Slingram electromagnetic surveys were conducted at the UNESCO World Heritage Site of Songo Mnara, Tanzania, as part of a multinational programme of investigation to examine the uses of space within and outside of this stonetown. The town was a major Islamic trading port during the fourteenth and fifteenth centuries. The surveys detected significant evidence for the containment of activities within the town walls, and previously unknown anthropogenic activity was revealed between the existing coral rag buildings, as well as within the open areas inside the town. Over 40 areas of magnetic disturbance were identified that corresponded directly with areas of high magnetic susceptibility in the Slingram electromagnetic in‐phase responses. On excavation many of these anomalies were found to correlate with wattle and daub structures, indicating a hitherto unidentified population, and the location of the anomalies also suggests a potentially deliberate delineation of space within the open areas of the stonetown. The combined results of the three geophysical data sets indicate that there are clear delineations in the use of space within Songo Mnara. This, coupled with the presence of industrial activities and evidence of more ephemeral occupation, neither of which had previously been recorded at the site, indicates that the pre‐existing town plan is in need of significant reappraisal. The current plan, based upon the remains of extant and collapsed coral buildings, can now be updated to incorporate the more ephemeral aspects of Swahili sites, including activity areas, and notably, the homes of the 'hidden majority' of the population. The results establish the benefit of a combined approach at these sites, and demonstrate that further invasive and non‐invasive exploration is required in order to fully exploit the significance of the role of geophysical techniques in understanding Swahili towns. © 2014 The Authors. Archaeological Prospection published by John Wiley & Sons Ltd.